Analysis of factors that influence the behavior of using complementary and alternative medicine (CAM) in chronic diseases - Liana, Yunita (Institute Of Computer Science (IOCS), 2024)
Complementary therapy is one of the treatment options that is often used by patients who face chronic diseases. Public interest in using Complementary and Alternative Medicines is increasing. The research aims to determine the most dominant factors influencing the use of Complementary and Alternative Medicines in the aggregate community with chronic diseases. This research design is cross-sectional. The research was conducted from 18 May to 17 June 2023. The sampling technique was purposive sampling, which was 107 people. The instrument is a questionnaire. Data were analyzed using the logistic regression test. The results of the multivariate analysis show that the most dominant variable influencing the use of Complementary and Alternative Medicines based on the odds ratio value is attitude where a positive attitude will increase the use of Complementary and Alternative Medicines by 9.384 times compared to a negative attitude after being controlled by other variables in modeling. The second most dominant variable is the length of time the chronic disease has been suffered, where the duration of the chronic disease suffered ? 3 months will increase the use of Complementary and Alternative Medicines by 8.454 compared to < 3 months after being controlled by other variables in the model.